Equivalence classes and local asymptotic normality in system identification for quantum Markov chains - Guţă, Mădălin; Kiukas, Jukka (Springer, 2015)
We consider the problem of identifying and estimating dynamical parameters of an ergodic quantum Markov chain, when only the stationary output is accessible for measurements. The starting point of the analysis is the fact that the knowledge of the output state completely fixes the dynamics up to an equivalence class of ‘coordinate transformation’ consisting of a multiplication by a phase and a unitary conjugation of the Kraus operators.